1992
DOI: 10.1520/jfs13337j
|View full text |Cite
|
Sign up to set email alerts
|

A Multidisciplinary Approach to the Detection of Clandestine Graves

Abstract: A multidisciplinary team that is comprised of professionals from industry, academia, and law enforcement who are studying methods to locate clandestine graves has been formed in Colorado. This article describes this team, research conducted, and preliminary results directed toward identifying the most effective means of locating buried bodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
128
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(132 citation statements)
references
References 8 publications
1
128
0
3
Order By: Relevance
“…cadavers) in terrestrial ecosystems has received increased attention due to pressing issues in forensic science and public health. An understanding of the fate of cadavers has implications for the estimation of postmortem interval (Vass et al, 1992), location of clandestine gravesites (France et al, 1992) and transmission and degradation of causative agents (Rapp et al, 2006). Although several studies have investigated the fate of the cadaver itself (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…cadavers) in terrestrial ecosystems has received increased attention due to pressing issues in forensic science and public health. An understanding of the fate of cadavers has implications for the estimation of postmortem interval (Vass et al, 1992), location of clandestine gravesites (France et al, 1992) and transmission and degradation of causative agents (Rapp et al, 2006). Although several studies have investigated the fate of the cadaver itself (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has tested the efficacy and applicability of different noninvasive geophysical technologies under controlled conditions in the detection of buried bodies, pig cadavers (70 kg average) and buried evidence (Davenport et al, 1988;Davenport et al, 1990;France et al, 1992;France et al, 1997). Conclusions from these studies indicate that GPR was the most important tool used to delineate graves and practical application by law enforcement investigators and geophysical contractors has confirmed these conclusions.…”
Section: Introductionmentioning
confidence: 84%
“…The changes to the visible appearance, chemical properties and biodiversity of the soil and surrounding environment are the result of soft tissue decomposition (France et al 1997 ;Carter et al 2007 ;. Investigators can utilize the changes that occur at a deposition site in order to aid in the detection and recovery of remains.…”
Section: Introductionmentioning
confidence: 99%